The "iron curtain" of anti-aging: what is behind it? - Mekan R. Orazov; Viktor E. Radzinsky; Evgeny D. Dolgov (LLC "MEDIAFORMAT", 2024)
Currently, the conditions associated with iron deficiency are one of the most pressing unresolved issue of anti-aging medicine. Female patients of late reproductive age and perimenopausal/postmenopausal patients represent the most "vulnerable cohorts" in terms of iron deficiency realization. To date, both short-term and long-term effects of iron deficiency associated with adverse consequences for health and the quality of life have been proven. The review considers the key determinants of iron deficiency development in female patients of late reproductive age and perimenopausal/postmenopausal patients, as well as clinical management of such patients based on domestic and international guidelines.